1997
DOI: 10.1121/1.419479
|View full text |Cite
|
Sign up to set email alerts
|

Spectral weights in level discrimination by preschool children: Analytic listening conditions

Abstract: In this series of experiments, adult and child listeners were required to attend to a target tone in the presence of two distracters and to indicate in which of two intervals the target tone had the higher level. The attentional weight listeners placed on each component was estimated by computing the correlation between the level change of each component across intervals and the listener's response. In the first experiment, weights were obtained as a function of the mean level of the distracters (250 and 4000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Even in these simple tasks, children up to the ages of 6 to 7 years perform more poorly than adults ͑Allen, 1991; Allen and Nelles, 1996;Wightman, 1992, 1995;Allen et al, 1989;Bargones and Werner, 1994;Bargones, Werner, and Marean, 1995;Schneider et al, 1989;Stellmack et al, 1997;Wightman and Allen, 1992;Willihnganz et al, 1997͒. However, simple tone detection paradigms do not present the kind of source segregation challenge that we face in real life, primarily because the "distraction" is typically relatively static and has a very different quality than the target signal.…”
Section: Introductionmentioning
confidence: 92%
“…Even in these simple tasks, children up to the ages of 6 to 7 years perform more poorly than adults ͑Allen, 1991; Allen and Nelles, 1996;Wightman, 1992, 1995;Allen et al, 1989;Bargones and Werner, 1994;Bargones, Werner, and Marean, 1995;Schneider et al, 1989;Stellmack et al, 1997;Wightman and Allen, 1992;Willihnganz et al, 1997͒. However, simple tone detection paradigms do not present the kind of source segregation challenge that we face in real life, primarily because the "distraction" is typically relatively static and has a very different quality than the target signal.…”
Section: Introductionmentioning
confidence: 92%
“…The paradigm used here shares some features with COSS analysis (Berg, 1989), where weights describing the combination of information are derived based on the relationship between random variability in some aspect of the stimulus and the probability of a signal-present response. This general approach has been used in previous studies of informational masking (Doherty & Lutfi, 1999;Neff & Odgaard, 2004;Stellmack, Willihnganz, Wightman et al, 1997). The model underlying the COSS analysis assumes that independent information is combined linearly across weighted channels.…”
Section: Experiments 2: Error Patternsmentioning
confidence: 99%
“…Introducing a masker level rove in this paradigm has little or no additional effect on pure tone detection threshold provided those maskers are sufficiently remote from the signal frequency to minimize energetic masking (Neff & Callaghan, 1988;Oh & Lutfi, 1998). Masker level uncertainty is associated with substantial informational masking for masked intensity discrimination, however (Buss, 2007;Doherty & Lutfi, 1999;Fantini & Moore, 1994;Stellmack, Willihnganz, Wightman et al, 1997). For example, a recent study by Buss (2007) showed that intensity discrimination threshold of a 50-dB SPL standard tone at 948.7 Hz was elevated by approximately 10 dB (10log(ΔI/I)) with the inclusion of masker tones at 300 and 3000 Hz, roved in level on each interval (50 dB SPL ±8 dB).…”
Section: Introductionmentioning
confidence: 99%
“…These properties include the slope of the function (Allen and Wightman, 1994) and the extent to which performance at high stimulus levels falls short of perfection (Bargones et al, 1995). In more recent work, auditory spectral distractors (Stellmack et al, 1997;Oh et al, 2001) and informational masking approaches (Wightman and Kistler, 2005) have been used to show immature selective attention in children. Generic, non-psychoacoustic measures of attention, such as the TEA-Ch (Manly et al, 2001), have also revealed immature auditory attention in subtests aimed at specific attentional functions (e.g.…”
Section: Introductionmentioning
confidence: 98%